Development Of High Iron And High Energy Snack Bar: Nutritional Content Analysis And Sensory Evaluation - Zainol Abidin, Nurul Alyani (Enhanced Knowledge in Sciences and Technology, 2021)
A snack bar is gaining interest from community due to its functional benefits. Either it is high in calories for energy or protein for muscle gain. In this growing market, it is important to seize the open opportunity. High energy bar is common in the market. However, not with high iron. The aim for this study is to develop energy bar with high level of both calories and iron. Besides, it is also to evaluate the acceptance on the snack bar when added with the additional ingredients. The additional ingredients used in this development are, Moringa oleifera seeds, green pumpkin seeds, apricots, and cranberries. Design expert mixture design was utilized to optimize the formulation of these ingredients. The results show formulation 2 with the highest calories (0.53 cal/g) and iron content (0.55 mg/L) while formulation 3 has the lowest for calorie (0.41 Cal/g) and formulation 1 has the lowest for iron content (0.24 mg/L). Overall, formulation 2 consist of 7.2% protein content, 42.9% total sugar content, 14.9% total fat content, and 2.1% dietary fiber. In conclusion, the proximate analysis of protein, fat and sugar content exceeded the value of previous research, but dietary fiber, iron and energy content does not exceed as the value of previous research was 100 g or per serving. In addition to the nutritional content analysis, the sensory evaluation is showing a positive acceptance from the consumers.